PERAN PERAWAT DALAM PENCEGAHAN DEEP VENOUS THROMBOSIS TINJAUAN EVIDENT BASED PRACTICE - Martiningsih Martiningsih (poltekkes kemenkes mataram, 2014)
Abstract: Deep vena thrombosis (DVT), which is also called as trombo emboli vena is the formation of one or more blood clot on vena in the body. DVT can engender the emboli pulmonal (Pulmonary Embolism/PE) where the blood clot is released or carried in the blod circulation system to the lungs, so that it empedes the blood supply for lungs and causes the lungs network necrousis. PE is a heavy complication of DVT and it is one of the preventable death causes on the hospitalized medical patient at the hospital. Generally, DVT happens at a lower extremity and causes vena insufficiency. The nurse role is needed in monitoring and observing the antikuogulant theraphy and a non-drug intervention, early mobilisation after the surgery, Range of Motion exercise, and the changing of the life style. Therefore, the nurse needs to brush up their knowledge based on the existing evidents (evident based) related to DVT prevention. The nurse could do study properly, give education for medical patients.